2018
DOI: 10.1038/s41408-018-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of apurinic/apyrimidinic nucleases in the regulation of homologous recombination in myeloma: mechanisms and translational significance

Abstract: We have previously reported that homologous recombination (HR) is dysregulated in multiple myeloma (MM) and contributes to genomic instability and development of drug resistance. We now demonstrate that base excision repair (BER) associated apurinic/apyrimidinic (AP) nucleases (APEX1 and APEX2) contribute to regulation of HR in MM cells. Transgenic as well as chemical inhibition of APEX1 and/or APEX2 inhibits HR activity in MM cells, whereas the overexpression of either nuclease in normal human cells, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 52 publications
7
56
0
Order By: Relevance
“…Consistently, we have demonstrated that inhibition of HR in EAC cells, inhibits genomic instability 14 and tumor growth 17 . Our recent data in multiple myeloma has also demonstrated that inhibition of APEX1 nuclease, a gene which drives genomic evolution in myeloma, increases cytotoxicity while inhibiting genomic instability caused by a chemotherapeutic agent 41 . We have made similar observations when HR inhibitors are used in combination with other chemotherapeutic agents (unpublished data).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Consistently, we have demonstrated that inhibition of HR in EAC cells, inhibits genomic instability 14 and tumor growth 17 . Our recent data in multiple myeloma has also demonstrated that inhibition of APEX1 nuclease, a gene which drives genomic evolution in myeloma, increases cytotoxicity while inhibiting genomic instability caused by a chemotherapeutic agent 41 . We have made similar observations when HR inhibitors are used in combination with other chemotherapeutic agents (unpublished data).…”
Section: Discussionmentioning
confidence: 89%
“…HR activity was measured in a plasmid substrate, using a luminescence-based assay reported by us previously 14,17,41 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this, our series of studies using Xenopus egg extract system suggest that APE2 plays a direct role in SSB repair via the 3′-5′ SSB end resection 11,26,43 . Of note, gene expression of APE2 and APE1 has been found up-regulated in multiple myeloma (MM) patients and MM cells, which may lead to dysregulation of HR via regulating Rad51 expression 32 . These new evidences suggest that APE2 contributes to genome integrity via different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested that abnormal expression of APE1 is implicated in cancer such as gastric cancer and ovarian cancer [29][30][31] . Both APE1 and APE2 have previously been found to be upregulated in multiple myeloma cell lines 32 . However, it remains unknown whether the expression of APE2 in patient-derived tumor tissues is altered when compared with non-malignant tissues across multiple cancer types.…”
mentioning
confidence: 97%